Neerslag van die Anglo-Boereoolog (1899-1902) in die Portugese geskiedskrywing - Ferreira, O. J. O. (Faculty of Humanities, University of the Free State, 2011)
This article traces how the Anglo-Boer War (1899-1902) was chronicled in Potuguese historiography. Considering that the Portuguese colony of Mozambique shared a border with the South African Republic (Zuid-Afrikaansche Republiek – ZAR), and that Lourenço Marques was a strategic harbour during the war, Portugal was, unwillingly, involved in the conflict, directly and indirectly. King Carlos I and the Portuguese government were pro-British, but many Portuguese newspapers, intellectuals and ordinary citizens were pro-Boer. One could have expected that the war would feature fairly prominently in Portuguese historiography, but this is not the case. From 1899 to 1906, during and directly after the war, a few publications – most of which were pro-Boer – were published. However, three decades passed before studies about the war trickled through from 1936 to 1971 – probably as a result of the stormy political history being played out in Portugal during that period. Only since 1984 have sporadic scientific studies about the Anglo-Boer War been undertaken in Portuguese, but the centenary of the war (1999-2002) itself passed almost unnoticed in Portugal.
Keywords: Anglo-Boer War (1899-1902); Portuguese government; Potuguese historiography